Degradación física de los principales cursos hídricos superficiales debido a monocultivos de Musa sp. (banano) y Theobroma sp. (cacao) en el cantón Valencia, provincia de Los Ríos - Vera Macías, María Cristina (2022)
The water resource is under increasing pressure due to population growth, economic activity and increased competition between users; Water intakes have increased twice as fast as population growth and today one-third of the world's population lives in countries experiencing medium to high water stress; Pollution